Use of Radiometric Dating Techniques to Determine the Age of Human Fossils - Matande, Pebri Aqli Saputra; Indriani, Sartika; Sarmila; Insani, Mujahidah Nur; Ansar, Asnaeni (Physics Department, Faculty of Mathematics and Natural Sciences, Universitas Negeri Makassar, 2025)
Dating ancient human fossils is a crucial component in reconstructing hominin evolution and migration. This article reviews the basic principles and applications of various radiometric dating techniques, including radiocarbon (14C), potassium-argon (K-Ar), uranium-series (U-Pb, U-Th), and advanced methods such as accelerator mass spectrometry (AMS) and laser ablation ICP-MS through a systematic literature review of primary and secondary sources. Data synthesis shows that the 14C method is effective for materials up to 50,000 years old, at the same time K-Ar and U-Pb/Th are suitable for older geological age ranges (hundreds of thousands to millions of years). Improved accuracy is supported by submicroscopic isotope analysis technology; however, the challenges of sample contamination and limited amounts of authentic material still limit its widespread application. These findings underscore the importance of a multi-method approach to obtain reliable absolute ages for human fossils and provide recommendations for refining sample handling procedures and integrating relative data (stratigraphy, magnetostratigraphy) for more comprehensive temporal contextualization.